The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.7164/antibiotics.43.49
|View full text |Cite
|
Sign up to set email alerts
|

Production, isolation and structure determination of a novel .BETA.-glucosidase inhibitor, cyclophellitol, from Phellinus sp.

Abstract: In the course of our screening of /?-glucosidase inhibitor, a culture filtrate of a mushroom, Phellinus sp. strongly inhibited the enzymeactivity. The active substance wasisolated through charcoal separation, column chromatography and crystallization. Spectroscopic and crystallographic analysis revealed that it had a novel cyclitol structure, (15f,2i?,35f,4/?,57?,6i?)-5-hydroxymethyl-7oxabicyclo[4, l ,0]heptane-2,3,4-triol, and we named it cyclophellitol. It inhibited almond-derived /?-glucosidase with an IC50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(86 citation statements)
references
References 7 publications
3
82
0
1
Order By: Relevance
“…Phellinsin A was able to inhibit the growth of fungi such as Colleotrichum lagenarium, Pyricularia oryzae, Rhizoctonia solani, Aspergillus fumigatus and Trichophyton mentagrophytes (Hwang et al 2000). Several studies have showed that Phellinus species can produce substances with cytotoxic (Atsumi et al 1990, 1993, Withers & Umezawa 1991, Han et al 1999, immunomodulatory (Song et al 1995, Kim et al 1996, antiviral (Walder et al 1995), antioxidant, antihepatotoxic (Ajith & Janardhnan 2002) activities.…”
Section: Resultsmentioning
confidence: 99%
“…Phellinsin A was able to inhibit the growth of fungi such as Colleotrichum lagenarium, Pyricularia oryzae, Rhizoctonia solani, Aspergillus fumigatus and Trichophyton mentagrophytes (Hwang et al 2000). Several studies have showed that Phellinus species can produce substances with cytotoxic (Atsumi et al 1990, 1993, Withers & Umezawa 1991, Han et al 1999, immunomodulatory (Song et al 1995, Kim et al 1996, antiviral (Walder et al 1995), antioxidant, antihepatotoxic (Ajith & Janardhnan 2002) activities.…”
Section: Resultsmentioning
confidence: 99%
“…These in vivo data thus confirm the expression patterns observed in microarray analyses of micromass cultures. We stably transfected an HA-tagged human RGS2 expression vector into the chondrogenic cell line ATDC5 (Atsumi et al, 1990) and differentiated them for 18 d to further investigate the role of RGS2 expression in chondrocyte differentiation. Overexpression of RGS2 was confirmed by 1) RT-PCR using primers designed against the N-terminal HA-tag and the RGS2 coding region, and 2) Western blotting using an anti-HA antibody.…”
Section: Functional Validation Of Microarray Results: Rgs2 Regulates mentioning
confidence: 99%
“…[1,2] They may be divided into two categories, those containing six-and those containing five-membered carbon rings. Among the most prominent of the six-membered representatives are cyclohexane hexitols, such as inositol derivatives, [1b] and pseudosugars, [1f, 2, 3] such as cyclophellitol [4] and valienamine. [5] Structural analogues of the latter are constituents of compounds of key pharmacological interest, for example acarbose, [6] adiposin, [7] trestatin, [8] and amylostatin.…”
Section: In Memory Of Støphan D Gøromentioning
confidence: 99%